Accounting for Management Decisions / Second Edition - Arnold John; Hope Tony (Prentice Hall, 1990)
This book explains and illustrates the conceptual issues in designing and using useful management accounting systems. Preface, The Role of Management Accounting, Accounting and Decision Making, Wealth and Wealth Maximization in Decision Making, Appendix: Use of Compound Interest Tables, Risk and Uncertainty in Decision Making, Costs and Benefits for Decisions, Cost Behavior and Cost-Volume-Profit Analysis, Cost-Estimation, Pricing Decisions, Short-Term Operating Decisions and Scarce Resources: Linear Programming, Dual Prices and Opportunity Cost, Long-Term Decisions: The Net Present Value Rule, Long-Term Decisions: Internal Rate of Return and Other Methods, The Budgeting Process, The Master Budget and the Cash Budget, Variance Analysis and Standard Costing, Divisional Performance, Summary and Revie, Compounding and Discounting Tables, Index.